Perception of and adaptation to climate change by farmers in the Nile basin of Ethiopia - Deressa, Temesgen T.; Hassan, Rashid; Ringler, Claudia (Cambridge University Press, 2011)
The present study employed the Heckman sample selection model to analyse the two- step process of adaptation to climate change, which initially requires farmers' perception that climate is changing prior to responding to changes through adaptation. Farmers' perception of climate change was significantly related to the age of the head of the household, wealth, knowledge of climate change, social capital and agro-ecological settings. Factors significantly affecting adaptation to climate change were: education of the head of the household, household size, whether the head of the household was male, whether livestock were owned, the use of extension services on crop and livestock production, the availability of credit and the environmental temperature.